On Restriction Estimates for Discrete Quadratic Surfaces. (3rd February 2018) - Henriot, Kevin; Hughes, Kevin
Abstract: We obtain truncated restriction estimates of an unexpected form for discrete surfaces $$\begin{align*}S_N = \{\, ( n_1, …, n_d, R( n_1, …, n_d ) ) \, , \, n_i \in [-N, N] \cap {\mathbb{Z}} \, \}, \end{align*}$$ where $R$ is an indefinite quadratic form with integer matrix.